Solos da bacia de Taubaté (Vale do Paraíba): levantamento de reconhecimento. Séries monotípicas, suas propriedades genético-morfológicas, físicas e químicas Soils of Taubaté basin (Paraíba Valley) - F. C. Verdade (Bragantia, 1961)
A Bacia tie Taubaté corresponde a um «vale de afundimento», onde ocorreram sedimentações no período Terciário, estando atualmente moldada pelo rio Paraíba e seus tributários. A planície aluvial é extensa e de grande importância econômica para o Estado de São Paulo. No presente trabalho é apresentado o levantamento de reconhecimento dos solos da Bacia de Taubaté, cujas finalidades foram determinar as características fisicas e químicas das terras e sua extensão aproximada, visando fornecer dados para o planejamento geral de irrigação e drenagem, ao mesmo tempo que eram identificados os tipos de solos (séries monotipicas) para o levantamento detalhado que se processa a partir do município de Pindamonhangaba. As categorias dos solos foram estabelecidas até séries monotípicas, mas a delimitação no campo, em mapas na escala de 1:100 0()0. foi feita nas unidades chamadas associação de séries. Procurou-se grupar na mesma associação solos que, pertencendo ao mesmo grande grupo e formação geológica, tivessem no perfil igual distribuição de classes texturais. Alguns solos, devido à sua pequena extensão ou da ocorrência íntima com outros de associações diferentes, fugiram à regra preliminarmente exposta. O levantamento abrange uma área de 222 980 hectares, incluindo a planície aluvial, as sedimentações terciárias e pequena faixa pré-cambriana que orla a Bacia. Foram estudados 151 perfis, caracterizando 48 séries monotípicas, grupadas em 18 associações de séries. A associação de séries A é constituída de solos pertencentes a sub-ordem Latossolo, formados em sedimentos do Terciário com textura argilosa em todos os horizontes. Os perfis dêstes solos apresentam um horizonte A3 normalmente adensado e um B friável. Compreendem as séries monotipicas: Borda, Cajuru, Feital, Gleba, Guatemala, Pinda, Pinhão, Polêmica, Ponte Alta, Rapadura e Ronco. The Taubaté Basin represents a <<Rift Valley>> where sediments were deposited during the terciary period, and the present configuration is set-up by the Paraíba river and its tributaries. The flood plain occupies large areas of economical significance for the State of São Paulo. This work may be classified as a reconnaissance soil survey, whose main objetives were to determine the physical and chemical soil characteristics, the area occupied by soil units in such a way that it would be usefull for a general drainage and irrigation program of the basin. At same time the identification of soil types (as monotype-series) was done looking to a detailed soil survey which is in development. The unit identified in the field was a mono-type-series but for mapping they were grouped into series associations, whose boundaries were plotted in maps on the scale 1:100,000. The series association includes soils belonging to the same great soil group, same geological formation, and same distribution of textural classes in the profile. Some soils because of small occurrence and relative intricacy of soil pattern, did not follow the last criterion. The area studied by this survey is about 222,980 hectares, including the flood-plain, tlie terciary sediments and small strip of the pre-Cambriam formation. Data are presented for identification of the units on the ground (48 soil types or mono-type series), and the chemical and physics craracteristics for 151 profiles. The soil types were grouped into 18 series associations. The series association A groups soil belonging to the sub-order Latosol, with clay texture in profile, derived from the terciary sediments. They have dense A horizon and friable B, and they include 11 soil types. The series association B is classified as red-yellow podzolic soil, with origin in Terciary sediments, having nonclay texture in the A horizon and clay one in the B. Three soil types were identified. The series association C. with the same origin and texture distribution in the profile as the B are characteristic Latosol. It also has three soil types. As representative of an intergrarle (latosol and red-yellow podzolic soil) is the Tumirim soil type. It represents an unique monotype series of the soil association D, but it is expected that other soil types will be defined in the detailed soil survey. Its profile is less than 1 meter deep, and clayey throughout. The Tumirim soil type is derived from Terciary mottled clays. The series associations E includes soils with poor drainage. Three soil types were determined representing Latosol imperfectly drained. Low Humic Glei and Humic Glei. The Terraces are represented by three soil types, forming the series association F. The texture goes from medium to sandy. The clay alluvial soils are in the series association (j, representing five soil types. According the topography position, some color layers and the kind of texture below 60 cm deep they have phases. The series associations H, I and J were plotted in a map but after mapping was done, the criterion for alluvial non-clay soils was changed and now the scries associations represent seven soil types. Bog and half bog are grouped in the soil association M. representing muck and peat-muck soils. Four soil types were identified. In Pre-cambrian area two series associations, N and O, were studied without soil type definitions. The former includes latosols with clay texture and the latter belongs to red-yellow podzolic soils with the same texture as the N. South of the town São José dos Campos a wide sandy soil area is represented by the serie association P, and it developed from sand deposits of Terciary, The soil type Putins may be considered as representative of the area. The serie association Q, is a group of mono-type-series belonging to the serie associations A and N in a intricate pattern only showed in detailed maps. When the alluvial soils are in a topographic position above the flood and the water table is almost permanently below one meter deep the soil types are grouped in the associations R and S. The lormer are non-clayed soil and the latter, clayey soils. Other soils considered as local occurrance are described.